Assessment of Potential Live Kidney Donors and Computed Tomographic Renal Angiograms at Christchurch Hospital - Thamer Alsulaiman; Stephen Mark; Sarah Armstrong; David McGregor (Advances in Urology)
Aims. To examine the outcome of potential live kidney donors (PLKD) assessment program at Christchurch Hospital and, also, to review findings of Computed Tomographic (CT) renal angiograms that led to exclusion in the surgical assessment. Methods. Clinical data was obtained from the database of kidney transplants, Proton. Radiological investigations were reviewed using the hospital database, Éclair. The transplant coordinator was interviewed to clarify information about PLKD who did not proceed to surgery, and a consultant radiologist was interviewed to explain unfavorable findings on CT renal angiograms. Results. 162 PLKD were identified during the period January 04–June 08. Of those, 65 (40%) proceeded to have nephrectomy, 15 were accepted and planned to proceed to surgery, 13 were awaiting further assessment, and 69 (42.5%) did not proceed to nephrectomy. Of the 162 PLKD, 142 (88%) were directed donors. The proportion of altruistic PLKD who opted out was significantly higher than that of directed PLKD (45% versus 7%, P=0.00004). Conclusions. This audit demonstrated a positive experience of live kidney donation at Christchurch Hospital. CT renal angiogram can potentially detect incidental or controversial pathologies in the kidney and the surrounding structures. Altruistic donation remains controversial with higher rates of opting out.